Revisiting Stake's model in TIMSS 2023: Exploring curricular contingencies through multilevel modeling - Yucel-Toy, Banu; Hunter, Darryl (ELSEVIER, 2026)
This study aims to demonstrate the use of TIMSS 2023 data within Stake's congruence and contingency curriculum evaluation model to examine relationships among antecedents, transactions, and outcomes in T & uuml;rkiye's 8th-grade mathematics curriculum using Multilevel Modeling. In this correlational study, data were collected from 141 schools, including 189 teachers and 4925 students, using context questionnaires and mathematics achievement test. Results indicated that principal, school, teacher, student, and instructional factors influence both transactions and outcomes. Instructional clarity, as a transaction variable, was significantly affected by teachers' education, students' sense of belonging, language, and fatigue. Regarding cognitive and affective outcomes, effective antecedent variables included home educational resources, absenteeism, school emphasis on academic success, principal and teacher education. Significant transaction variables included teaching limited by students not ready, instructional clarity, and homework. This approach demonstrates how TIMSS data can inform curriculum evaluation and improvement by revealing the complex interplay of contextual and instructional factors.
Keywords: Curriculum evaluation; Stake's congruence-contingency model; TIMSS; Multi-level analysis; MATHEMATICS ACHIEVEMENT; ACADEMIC-ACHIEVEMENT; INSTRUCTOR CLARITY; STUDENT; HOMEWORK; PERFORMANCE; ELEMENTARY; PRINCIPALS; MOTIVATION; ATTENDANCE; Education & Educational Research; Psychology